2013
DOI: 10.1038/onc.2013.48
|View full text |Cite
|
Sign up to set email alerts
|

Mapping genetic alterations causing chemoresistance in cancer: identifying the roads by tracking the drivers

Abstract: Although new agents are implemented to cancer therapy, we lack fundamental understandings of the mechanisms of chemoresistance, the main obstacle to cure in cancer. Here we review clinical evidence linking molecular defects to drug resistance across different tumour forms and discuss contemporary experimental evidence exploring these mechanisms. Although evidence, in general, is sparse and fragmentary, merging knowledge links drug resistance, and also sensitivity, to defects in functional pathways having a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 267 publications
(263 reference statements)
1
42
0
Order By: Relevance
“…Among TP53 wild-type breast cancers revealing primary resistance to anthracyclines, mutations in the p53 upstream activator CHEK2 [23] or low expression levels of ATM [24] have been observed. Yet, additional factors are known to influence p53 activation in response to genotoxic stress [25, 26]. One such factor is the PTEN protein encoded by the PTEN gene [10].…”
Section: Discussionmentioning
confidence: 99%
“…Among TP53 wild-type breast cancers revealing primary resistance to anthracyclines, mutations in the p53 upstream activator CHEK2 [23] or low expression levels of ATM [24] have been observed. Yet, additional factors are known to influence p53 activation in response to genotoxic stress [25, 26]. One such factor is the PTEN protein encoded by the PTEN gene [10].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a study targeting chemoresistant breast cancer cells following neo-adjuvant chemotherapy, we found that some patients achieved pathological complete response (pCR; defined as no residual invasive cancer in the breast and lymph nodes), which would be expected to be associated with a more favorable prognosis than that in patients who did not achieve pCR (13). Chemoresistance involves numerous complex mechanisms, including gene pathways associated with apoptosis/senescence and DNA repair, which are often influenced by communication between host and tumor cells (14). Furthermore, EMT, anti-apoptotic mechanisms, and stemness induced by the cancer microenvironment have been shown to play important roles in chemoresistance (15).…”
Section: Introductionmentioning
confidence: 99%
“…Chemoresistance, both intrinsic and acquired, is a main cause of recurrences or failure of current treatment 2 . Up to date, several factors contributed to the development of chemoresistance including genetic alterations 3 , altered drug accumulation 4 , drug-target amplification 5 , and autophagy 6 . Many cellular signaling pathways have been studied to explore the mechanism of chemoresistance of osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%